Ask your doctor or pharmacist!: On the effect of self-dispensing physicians on pharmaceutical coverage - Matthias Bannert; David Iselin (ETH Zurich, KOF Swiss Economic Institute, 2015)
In most developed countries drugs are dispensed to patients through physicians and pharmacists. This paper studies the effects of allowing doctors to directly dispense drugs to patients (self-dispensation) on pharmaceutical coverage. We use a Swiss dataset in our empirical analysis because Switzerland's federalist legislation allows us to study self-dispensing and non-self-dispensing regimes alike. We add location information obtained from Google Geocoding services to our dataset in order to measure coverage based on distances. To capture a driver of long term positioning decisions, we take revenues as a proxy for a pharmacy's usage rate. We find that, ceteris paribus, self-dispensation leads to a lowered regional density of pharmacies. By matching similar pharmacies across both regimes we find that revenues are substantially lower for pharmacies under a self-dispensation regime. Pharmacies in cantons that allow physicians to dispense drugs tend to have relatively higher revenues associated with non-drugs. We suggest to organize legislation on self-dispensation at a fine grained regional level as regional typologies are the most reasonable justification for regime choice.
Keywords: I18; I11; C21; 330; pharmaceutical coverage; drug dispensation; self-dispensation; health care expenditures; GIS; Propensity Score Matching